Investigating the Dynamics of Learning Discipline and Environment on the Academic Outcomes of Class X TAV Students at SMKN 1 Linggo Sari Baganti - Ravi Syaputra; Almasri; Thamrin; Delsina Faiza (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This research aims to assess the extent of the contribution of study discipline and learning environment to the learning outcomes of Class X TAV students at SMKN 1 Linggo Sari Baganti. The research method employed is descriptive correlational, with a population of 49 students and a sample of 33 Class X TAV students selected randomly through Simple Random Sampling. Learning outcomes data were obtained from the Electronics Basics subject teacher, while data on study discipline and learning environment were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. Data analysis was conducted using the SPSS program. The results of the research indicate that study discipline (X1) contributes 15.9% to learning outcomes, while the learning environment (X2) contributes 15.3%. Together, study discipline (X1) and the learning environment (X2) jointly contribute 21.3% to student learning outcomes (Y). These results suggest that higher levels of study discipline and a conducive learning environment are associated with better student learning outcomes. The implications of this research underscore the importance of efforts to enhance students' study discipline and create a conducive learning environment to improve their learning outcomes.